Incidence, risk factors and clinical implications of chyle leak after pancreatic surgery - Strobel, Oliver; Brangs, Susanne; Hinz, Ulf; Pausch, Thomas; Hüttner, Felix; Diener, Markus K.; Schneider, Lutz; Hackert, Thilo; Büchler, Markus W. (The British journal of surgery, 2016)
Background Chyle leak is a well known but poorly characterized complication after pancreatic surgery. Available data on incidence, risk factors and clinical significance of chyle leak are highly heterogeneous. Methods For this cohort study all patients who underwent pancreatic surgery between January 2008 and December 2012 were identified from a prospective database. Chyle leak was defined as any drainage output with triglyceride content of 110 mg/dl or more. Risk factors for chyle leak were assessed by univariable and multivariable analyses. The clinical relevance of chyle leak was evaluated using hospital stay and resolution by 14 days for short-term outcome and overall survival for long-term outcome. Results Chyle leak developed in 346 (10·4 per cent) of 3324 patients. Pre-existing diabetes, resection for malignancy, distal pancreatectomy, duration of surgery 180 min or longer, and concomitant pancreatic fistula or abscess were independent risk factors for chyle leak. Both isolated chyle leak and coincidental chyle leak (with other intra-abdominal complications) were associated with prolonged hospital stay. Some 178 (87·7 per cent) of 203 isolated chyle leaks and 90 (70·3 per cent) of 128 coincidental chyle leaks resolved with conservative management within 14 days. Initial and maximum drainage volumes were associated with duration of hospital stay and success of therapy by 14 days. Impact on survival was restricted to chyle leaks that persisted at 14 days in patients with cancer undergoing palliative surgery. Conclusion Chyle leak is a relevant complication, with an incidence of more than 10 per cent after pancreatic surgery, and has a major impact on hospital stay. Drainage volume is associated with hospital stay and success of therapy.